Eliciting social stressors, supports, and determinants of health through the DSM-5 cultural formulation interview - Aggarwal, Neil Krishan; Chen, Daniel; Lewis-Fernández, Roberto (Frontiers in Psychiatry, 2023)
Objective: As recognition of the importance of social determinants of mental health has increased, the limitations of clinical competence-enhancing interventions that do not emphasize this approach have emerged. The Cultural Formulation Interview (CFI) is a cultural competence intervention that emerges from a confluence of social medicine and medical anthropology traditions. Limited research has examined how patients respond to CFI questions on social-structural aspects of illness and care to assess whether the CFI adequately elicits information on social determinants of mental health. Methods: Patients’ responses during a first intake appointment to three CFI questions on social stressors, supports, or barriers to care from 27 patient-clinician dyads are analyzed through qualitative content analysis. The data come from a hyper-diverse clinical setting in Queens, New York, where no ethnoracial group has a majority and all patient-clinician dyads reflect cross-cultural interactions. Results: At least one social determinant was coded in 89 of all cases, and nearly 44% included themes related to multiple determinants of health. The most-commonly coded theme was social relationships (n=21), followed by financial instability (n=7), stigma (n=5), housing instability (n=2), and poor access to healthcare, involvement in the criminal justice system, employment instability, area-level poverty, and immigration policies (n=1 each). Conclusion: Our work shows that social determinants of mental health can be elicited through the CFI. Future work should examine how this information is included in clinicians’ formulations and whether the cultural formulation approach would benefit from additional revision to facilitate assessment of socio-structural factors.